STRATEGI PEMBERDAYAAN KOMUNITAS LOMBOK INFLUENCER DALAM MENINGKATKAN DIGITAL MARKETING DI KOTA MATARAM - Rohin Novia Maydi Putri; Syafruddin Syafruddin; Imam Malik; Suud Suud (Universitas Hamzanwadi, 2025)
This research aims to: (1) identify and analyze the community empowerment programs of Lombok Influencer, (2) understand and analyze the community empowerment strategies of Lombok Influencer in enhancing digital marketing in the city of Mataram. This research uses a qualitative approach with a case study method. The data collection techniques used are observation, interviews, and documentation. The data analysis techniques in this research use data reduction, data presentation, and conclusion drawing techniques. The results of this study found that the Lombok Influencer community empowerment program includes: Skill training programs such as public speaking, voice over, start-up design, and digital creative skills training, as well as recognition and appreciation programs in the form of an influencer awarding night event. Then the community empowerment strategy of Lombok Influencer is building strong and authentic relationships through active interactions between management and community members in WhatsApp groups, organizing meetings with influencers; (2) providing resources and support in the form of skill training, community website provision, collaboration with business actors, community reward programs, (3) facilitating creative content in the form of freedom to create content concepts, and providing group digital marketing projects, (4) providing incentives in the form of community rate cards for commission distribution; (5) providing public recognition by promoting community members digital marketing content on social media, organizing influencer appreciation events. (6) performance monitoring in the form of controlling the progress of members performance.